Ten years of Women's Wellness research: Key lessons from conducting randomised controlled trials of a whole-of-lifestyle behavioural intervention - Sarah M. Balaam; Alexandra L. McCarthy; Natalie K. Vear; Mackenzie J. Petie; Debra J. Anderson; Janine P. Porter-Steele (Contemporary Clinical Trials Communications)
Many women are diagnosed with breast cancer and while the survival of this cohort has improved, their likelihood of developing treatment-related chronic conditions is considerable. Over the last 10 years, our research group has developed and refined a whole-of-lifestyle intervention, the Women's Wellness after Cancer Program (WWACP), for women who have finished treatment for primarily breast and gynaecological cancers. Culturally-specific iterations of this program were recently completed with younger breast cancer survivors (aged <50 years) living in Australia, New Zealand/Aotearoa and Hong Kong.Over the last decade, various approaches have been used to trial the WWACP, mostly randomised controlled trials. While this methodology is considered the gold standard to determine efficacy in health and medical research, its limitations in our interventional research are apparent. In this opinion article, we discuss these limitations as well as alternative options for the appropriate testing of behavioural studies in women treated for cancer. We also discuss how the contribution of informed consumer advocates and participant consumers has influenced changes to our study designs.